Species-specific kinetics and zonation of hepatic DNA synthesis induced by ligands of PPARα - Al Kholaifi, Abdullah; Amer, Abeer; Jeffery, Brett; Gray, Tim J.B.; Roberts, Ruth A.; Bell, David Robert (Oxford University Press, 2008)
PPARα ligands evoke a profound mitogenic response in rodent liver, and the aim of this study was to characterise the kinetics of induction of DNA synthesis. The CAR ligand, 1,4-bis[2-(3,5- dichoropyridyloxy)]benzene, caused induction of hepatocyte DNA synthesis within 48 hours in 129S4/SvJae mice, but the potent PPARα ligand, ciprofibrate, induced hepatocyte DNA synthesis only after 3 or 4 days dosing; higher or lower doses did not hasten the DNA synthesis response. This contrasted with the rapid induction (24 hours) reported by Styles et al. (Carcinogenesis 9:1647-1655). C57BL/6 and DBA/2J mice showed significant induction of DNA synthesis after 4, but not 2, days ciprofibrate treatment. Alderley Park and 129S4/SvJae mice dosed with methylclofenapate induced hepatocyte DNA synthesis at 4, but not 2, days after dosing, and proved that inconsistency with prior work was not due to a difference in mouse strain or PPARα ligand. Ciprofibrate-induced liver DNA synthesis and growth was absent in PPARα- null mice, and are PPARα-dependent. In the Fisher344 rat, hepatocyte DNA synthesis was induced at 24 hours after dosing, with a second peak at 48 hours. Lobular localisation of hepatocyte DNA synthesis showed preferential periportal induction of DNA synthesis in rat, but panlobular zonation of hepatocyte DNA synthesis in mouse. These results characterise a markedly later hepatic induction of panlobular DNA synthesis by PPARα ligands in mouse, compared to rapid induction of periportal DNA synthesis in rat.